Pertussis in infants: how to protect the vulnerable? - Chuk, Lai-man R; Lambert, Stephen B; May, Meryta L; Beard, Frank H; Sloots, Theo P; Selvey, Christine E; Nissen, Michael D (Communicable Diseases Intelligence, 2008)
In terms of adverse outcomes, infants remain the group most vulnerable to severe pertussis disease. Adult household contact is thought to be the main source of transmission to infants. This study reviews exposure history, vaccination status, admission outcome and quality of discharge coding of hospitalised infants with pertussis at a tertiary paediatric hospital. We identified cases between 1997 and 2006 from 2 sources: hospital discharge coding and positive Bordetella pertussis results from the hospital laboratory database. We assessed the completeness of each of these sources, compared with the dataset of all identified cases. We identified 55 hospitalised infants with pertussis. The 35 cases (64%) less than 3 months of age had greater risk of Intensive Care Unit admission, higher mortality, and were more likely to have parents as an identified source. On admission, only 5 cases (9%) were more than 2 weeks overdue for their previous scheduled pertussis vaccination. Discharge coding was more sensitive for identifying cases than the laboratory database. Nine cases (16%) had incorrect discharge coding. Even infants up to date for pertussis vaccine can have severe disease requiring hospitalisation. Immunising parents planning to have, or who have had, a newborn baby may help to prevent pertussis in infants. Commun Dis Intell 2008;32:449–456.